Functional and structural characterization of mouse Factor H-related B protein unveils a novel dimerization domain shared by FHR-B and FH - Martín-Ambrosio Doménech, Adrián; González Sanz, Silvia; Márquez Tirado, Bárbara; Juana-López, Lucia; Goicoechea de Jorge, Elena; Rodríguez de Córdoba, Santiago; Martín Merinero, Héctor (Frontiers in Immunology, 2025)
Factor H-related proteins (FHRs) are found in mice, but their equivalence to human FHRs remains uncertain. This study identifies three FHRs in mouse plasma (FHR-B, FHR-C, and FHR-E) and focuses on characterizing FHR-B. Using purified plasma proteins and recombinant mutants, FHR-B was found to form dimers and bind strongly to C3, C3b, iC3b, and C3dg. It also competes with mouse Factor H (mFH) for binding to C3b-coated surfaces and disrupts mFH regulation in hemolysis assays with sheep and guinea pig erythrocytes. These functions are localized to the C-terminal region and are dependent on FHR-B dimerization. Dimerization occurs through the N-terminal region (SCR1-3), which differs from mFH SCR5-7 by only four amino acids and also shares significant homology with human FHR-3 and human FH SCR5-7. In contrast to FHR-1, AUC experiments indicate that FHR-B dimerization is pH-sensitive, reversible and that the monomers in the dimer present the same head to tail orientation. Mutant analyses revealed that mFH SCR5-7 also forms dimers, but less efficiently than FHR-B. Notably, substituting FHR-B Tyr162 (a key residue homologous to the disease-associated Tyr402 in human FH) for His reduces dimerization. We also found that a recombinant FHR-B with a duplicated dimerization domain formed stable dimers but lacked functional activity. Overall, FHR-B shows structural and functional similarities with various human FHRs, suggesting convergent evolution between mouse and human FHRs. Furthermore, this study reveals a novel dimerization domain shared by FHR-B and mouse FH and illustrates the importance of dimerization and monomer orientation in FHRs activity. It also underlines notable differences between human and mice FHRs that should be further explored before modeling FHR-associated human diseases in mice.